A comparison of two digital techniques for the fabrication of complete removable dental prostheses: a pilot clinical study - Schwindling, Franz Sebastian; Stober, Thomas (The journal of prosthetic dentistry, 2016)
STATEMENT OF PROBLEM: The introduction of digital techniques might improve the quality and cost-effectiveness of treatment with complete removable dental prostheses (CDs). PURPOSE: The purpose of this pilot clinical trial was to study and compare the clinical feasibility, complications during fabrication, and quality of 2 types of digitally designed CDs. MATERIAL AND METHODS: Five participants were recruited into this preliminary clinical trial. For each participant, 2 pairs of digital CDs were designed. Prosthesis bases were fabricated by using identical data, either by milling from polymethyl methacrylate blanks or by injection molding. The treatment involved 4 clinical appointments. Polyvinyl siloxane impressions were made with custom trays and were subsequently digitalized. After evaluating esthetics and function with trial dentures, the CD bases were fabricated. To evaluate the workflow and quality of the prostheses, the clinical outcome was measured on 6-point scales ranging from poor (grade 6) to excellent (grade 1). For both prosthesis types, the following aspects were examined: fit, retention, esthetics, phonetics, maxillomandibular relation, and occlusion. RESULTS: Both types of digital CDs could be fabricated without major complications. Only a few minor complications occurred during the fabrication process, predominantly esthetic issues. No pronounced difference was found between the prostheses concerning functional aspects. The definitive esthetic outcome was rated as very good. CONCLUSIONS: The CDs fabricated using digital technology met the clinical requirements. However, more research is needed to confirm the results of this investigation.
Gesehen am 23.11.2017